(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The India is an agriculture-based country, infection by microorganisms such as fungi, bacteria, or other lower-class organisms is a major issue for obtaining a high-quality crop, and it will have an impact on both the quality and quantity of production. The ergot is one of the common diseases seen in cereal crop caused by fungus Claviceps purpurea, and Secale cornutum is a homoeopathic medicine prepared from Claviceps purpurea fungus infected rye plants. Homoeopathy is a science originated on the principle of "Similia Similibus Curenture" and by application of this principle; authors have conducted in vitro study with an aim to check the efficacy of the homoeopathic drug Secale cornutum against the fungal infection Claviceps purpurea. Potato Dextrose Agar (PDA) mixed with distilled water and slightly heated the mixture through water bath to mix it well, then 13 PDA agar plate was prepared, out of which 4 duplicate plates were prepared for various potencies (Q, 30C, 200C, 1M) of Hom. Medicine Secale cornutum . Four agar plates and their four duplicates were treated with homoeopathic medicine Secale cornutum with potencies of Q, 30C, 200C, 1M. A serial dilution of active control fungicide crapton was prepared with 1ml of water of 10-1, 10-2, 10-3, 10-4, 10-5and 10-6 out of which three agar plates were treated with serial dilution of active control of 10-1, 10-3, and 10-6. One plate was treated with alcohol and one plate for negative control. Optimum density (OD) of fungus culture was prepared and 50 mules of 1 OD was diffused with each agar plate. To observe the zone of inhibition three wells of 8mm diameter were inserted in each plate, and kept those at 25°C in incubator for 72 hrs. In this research, only the serial dilutions of active control crapton 10-1 and 10-3 showed zones of inhibition of 38mm and 26mm, respectively, but none of the potencies (Q, 30C, 200C, 1M) of homoeopathic medicine Secale cornutum, showed any zone of inhibition. Inhibition and /or control of the infection using of homoeopathic medicine was our prime objective so we have explored antifungal activity of various potency Q, 30C, 200C, and 1M of Secale cornutum . It will take more researches to find out another homoeopathic medicine having antifungal activity on pathogenesis of Claviceps purpure.